Self-Efficacy dan Motivasi Siswa dalam Pembelajaran Pendidikan Jasmani: Scoping Review - Prabowo, Trisnar Adi; Afifah, Mar'atul; Cahyo, Febriansyah Dwi; Zakaria, Achmad; Indarto, Asyidika Vito (Universitas Hamzanwadi, 2025)
The purpose of this study through to analyze how self-efficacy and motivation can influence physical education outcomes. The scoping review method was used in this study, to cartographize the existing literature, identify research gaps, and formulate recommendations for more effective physical education practices as well as for future research. The research identification was determined to be how self-efficacy and motivation affect students' participation and achievement in physical education. The literature search came from PubMed, Education Resources Information Center (ERIC), PsycINFO, Scopus, Web of Science and Google Scholar with various keywords that have been determined. While the criteria for articles are discussing self-efficacy or motivation in the context of physical education, studies conducted on elementary, junior high, or senior high school students, articles in English, articles published between 2015 - 2025, articles have open access. The results of this study found a total of 8 articles that were suitable for data synthesis and analysis. This research describes demonstrates the importance of innovation in physical education teaching methods to increase students' self-efficacy and motivation. The use of exergames, hybrid pedagogical models such as Teaching Games for Understanding (TGfU) and Sport Education (SE), and increased Physical Education (PE) sessions had a positive impact on student engagement and achievement. However, long-term evaluation and further research with longitudinal designs and objective measurement instruments are needed to overcome the methodological limitations of previous studies. Educators need to implement innovative methods that support students' intrinsic motivation and improved motor competence.